Toward the valorization of our anthropological and paleopathological heritage. The musealization of the osteoarchaeological contexts - Licata, Marta; Larentis, Omar; Badino, Paola; Fusco, Roberta; Tesi, Chiara (Medicina Historica, 2020)
The musealization of the osteological finds inside the archaeological context is a proposal of our Center of Research and concerns the enhancement and promotion of the archaeological heritage of our territory. The creation of Laboratories of Physical Anthropology and Paleopathology ,set up directly on the archaeological sites of necropolis once the anthropological study is completed, will realize a visibility of its operation, proposing precisely the restoration and museum display of the osteoarchaeological finding. The project will activate local development processes that will improve tourist attraction of the archaeological site and implement strategies that integrate the site with other resources and socio-economic structure of the area.